Analisis Penerapan Asas Ultimum Remedium terhadap Anak Pelaku Tindak Pidana Persetubuhan: Studi Putusan Nomor: 15/Pid.Sus Anak/2022/PT.Sby - Khairani Aisya Amira Siregar; Dona Raisa Monica; Emilia Susanti (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2024)
Purpose: This study aims to find out the basis of the judge's legal considerations in imposing sentences the ultimum remedium principle for children who commit the crime of sexual intercourse in the Study Decision Number: 15/Pid. Sus Anak/2022/PT, and to find out the implementation of applying ultimum remedium for children perpetrator of the crime of sexual intercourse. Methodology: The research method used in this study is a normative juridical law research method that uses scientific procedures to find truth based on legal scientific logic from a normative perspective. Results: Based on the results of the description and discussion above, it can be concluded that the judge's legal considerations did not apply the ultimum remedium principle to children who commit the crime of sexual intercourse in decision number 15/Pid. Sus Anak/2022/PT.Sby. In sentencing, the child perpetrator was sentenced to four years in prison with children who committed the crime of sexual intercourse in Study Decision Number 15/Pid. Sus Anak/2022/PT considers several things as juridical, non-juridical, burdensome, and relieving the perpetrator. Limitations: This study is related to how judges give consideration in a decision in a trial Contribution: This research is expected to be a reference and contribution in the application of criminal law